2006
DOI: 10.1359/jbmr.060701
|View full text |Cite
|
Sign up to set email alerts
|

Bone Material Properties in Trabecular Bone From Human Iliac Crest Biopsies After 3- and 5-Year Treatment With Risedronate

Abstract: Long-term effects of risedronate on bone mineral maturity/crystallinity and collagen cross-link ratio in triple iliac crest biopsies of osteoporotic women were evaluated. In this double-blinded study, 3-and 5-year treatment with risedronate arrested the tissue aging encountered in untreated osteoporosis and in osteoporosis treated with other antiresorptives. This effect may be contributing to risedronate's antifracture efficacy.Introduction: Risedronate is widely used in the treatment of osteoporosis. It reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 57 publications
4
63
3
Order By: Relevance
“…Although it was reported that there was an age-related increases in mineral crystallinity and that risedronate prevented this change in post-menopausal women [13], we did not detect difference in the crystal size between the aged OVX animals and those of age-match sham animals. Bisphosphonate treatments also did not seem to alter the crystal size.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Although it was reported that there was an age-related increases in mineral crystallinity and that risedronate prevented this change in post-menopausal women [13], we did not detect difference in the crystal size between the aged OVX animals and those of age-match sham animals. Bisphosphonate treatments also did not seem to alter the crystal size.…”
Section: Discussioncontrasting
confidence: 92%
“…Postmenopausal women were treated with oral risedronate or placebo for 5 years, and the average degree of bone mineralization, estimated from iliac crest biopsies, increased by 4.2% after 3 years of treatment, which was sustained for another 2 years [27]. Risedronate also prevented the age-associated and estrogen deficiency-related elevation in mineral maturity/crystallinity and collagen cross-link ratios [13]. In a study on human calcanei, Follet et al [4] found that the degree of bone mineralization is a determinant of bone strength after adjustment for bone volume and other bone microarchitecture parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Fourier-transformed infrared spectroscopy (FTIR), Durchschlag and colleagues (30) showed that BP treatment prevented the maturation of collagen found in patients not treated with BPs and reduced collagen maturity in newly formed bone. Boskey and colleagues (31) reported no change in collagen maturity in women treated with alendronate.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
“…This appeared to result from effects on active bone-forming areas. (13) The purpose of the present study was to investigate whether ALN and RIS exert different effects on bone material properties (mineral/matrix, mineral maturity/crystallinity, relative proteoglycan content, and pyridinoline [pyr]/divalent collagen crosslink ratio) during bone formation. To do this, iliac crest biopsies from patients who received either ALN or RIS were analyzed by Raman and Fourier transform infrared microspectroscopy (FTIRM).…”
Section: Introductionmentioning
confidence: 99%